2019
DOI: 10.1182/blood-2018-07-820712
|View full text |Cite
|
Sign up to set email alerts
|

New therapies using nonfactor products for patients with hemophilia and inhibitors

Abstract: Regular prophylaxis with factor VIII (FVIII) or FIX products to prevent bleeding in patients with severe hemophilia A (HA) and HB, respectively, results in marked suppression of the onset of arthropathy and contributes greatly to improvements in quality of life. Some issues remain with the use of clotting factor replacement therapy, however. The need for multiple IV infusions is associated with a substantial mental and physical burden, and the hemostatic effect of bypassing agents (BPAs) in patients with inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 69 publications
0
56
0
Order By: Relevance
“…In an effort to improve treatment options for PWH, a number of alternative therapeutic approaches have been explored in recent years (Callaghan et al , ). Emicizumab (Hemlibra; Chugai Roche) is a humanized bispecific antibody administered subcutaneously that has a half‐life of 3–4 weeks (Nogami & Shima, ). By binding to both FIXa and FX, emicizumab mimics the normal procoagulant cofactor role of FVIIIa.…”
Section: Targeted Inhibition Of Antithrombin Anticoagulant Effect By mentioning
confidence: 99%
See 2 more Smart Citations
“…In an effort to improve treatment options for PWH, a number of alternative therapeutic approaches have been explored in recent years (Callaghan et al , ). Emicizumab (Hemlibra; Chugai Roche) is a humanized bispecific antibody administered subcutaneously that has a half‐life of 3–4 weeks (Nogami & Shima, ). By binding to both FIXa and FX, emicizumab mimics the normal procoagulant cofactor role of FVIIIa.…”
Section: Targeted Inhibition Of Antithrombin Anticoagulant Effect By mentioning
confidence: 99%
“…By binding to both FIXa and FX, emicizumab mimics the normal procoagulant cofactor role of FVIIIa. Recent phase 3 clinical trials have demonstrated the clinical efficacy of emicizumab in patients with hemophilia A (Nogami & Shima, ). Consequently, emicizumab has recently been licensed in a number of different jurisdictions for prevention of bleeding episodes in patients with severe hemophilia A with or without FVIII inhibitors.…”
Section: Targeted Inhibition Of Antithrombin Anticoagulant Effect By mentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the bispecific antibody, emicizumab, which mimics the procoagulant function of activated FVIII (FVIIIa) has been approved in over 60 countries and now offers an effective option for prophylactic treatment for patients with hemophilia A irrespective of the presence of inhibitors. The efficacy of emicizumab in clinical trials was excellent, and tolerable safety was confirmed, although some adverse events, including thromboembolic TMA and neutralizing antidrug antibodies (ADAs) were reported in specific circumstances 10 . More recently, however, several questions have become apparent for the clinical use of emicizumab.…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacological approach to haemophilia is currently a dynamically changing area, and there are several reports on innovative and highly effective, though mechanistically distinct, treatment options. These new therapeutics might be likely guided by comprehensive molecular diagnosis in each case to justify treatment choice 2,8,9. Still, at this time of rapid technological advances, haemophilia remains an area with unanswered basic questions such as the impact of coagulation factor concentrate origin (recombinant vs plasma-derived) or brand on inhibitor development, and this cannot be addressed without genetic data 10.…”
mentioning
confidence: 99%